Developmental delay and dysmorphic features associated with a previously undescribed deletion on chromosome 1. Issue 8 (August 1995) - Barton, J S; O'Loughlin, J; Howell, R T; L'e Orme, R
Abstract : We report an 18 month old girl with developmental delay, dysmorphic features, and a karyotype 46, XX, del (1) (p32.1p32.3). To our knowledge the clinical features associated with this deletion have not been reported previously.